Advances in Targeted Therapies and Combination Approaches for Melanoma: A Comprehensive Review - Przestrzelska, Magda; Ślesicka, Iga; Zozula, Natalia; Tomczewska, Zuzanna; Rykucka, Aleksandra; Wąs, Marcin; Latała, Aleksandra; Kiełbasa, Justyna; Kowalczyk, Agata; Bil, Katarzyna (Quality in Sport, 2024)
Introduction and Purpose: Melanoma, an aggressive malignancy from melanocytes, has a poor prognosis. Despite advances in targeted therapies and immunotherapies, drug resistance remains a challenge. This review examines the molecular pathways involved in melanoma and therapeutic strategies targeting them, aiming to improve patient outcomes and overcome treatment resistance by understanding genetic alterations and signaling cascades driving melanoma progression. State of Knowledge: Melanoma arises from genetic predisposition and UV radiation exposure, involving mutations in pathways like RAS/RAF/MAPK and PI3K/AKT. Targeted therapies, such as BRAF and MEK inhibitors, are effective, especially in BRAF-mutant patients. However, resistance mechanisms, including alternative pathway activation and immune evasion, limit their long-term success. Combination therapies with immunotherapies show promise in overcoming resistance. Emerging targets like NRAS, c-KIT, and c-MET offer new treatment possibilities. Ongoing challenges include identifying biomarkers for patient stratification and managing treatment-related toxicity. Conclusions: Understanding the molecular mechanisms of melanoma is crucial for advancing therapies. Targeted therapies and combination approaches have improved outcomes, especially in advanced cases. However, challenges like treatment resistance and toxicity require ongoing research. By exploring signaling pathways and new targets, treatment efficacy and durability can be enhanced. Continued research and clinical trials are essential to translate these advancements into practice, improving survival rates and quality of life for melanoma patients.